Zur Beteiligung der an bei der Entstehung der Industriestadt Łódź im 19. Jahrhundert [On the involvement of the in the creation of the industrial city of Łódź in the 19th century] - Pytlas, Stefan (Studia Historiae Oeconomicae, 2009)
After Napoleon's defeat, the Duchy of Warsaw, a kind of substitute for the independent Polish state, was soon abolished. However, Poles in general pinned hopes on its now-defunct existence that their country would be able to regain its sovereignty in the not too distant future. This did not happen, and Russia was forced to form the Kingdom of Poland. After concluding an agreement with the other two partitioning powers in the resolutions of the Congress of Vienna on 29 June 1815, it accepted the existence of a Polish nation and the right to free trade within the borders of the former Polish Republic of 1772 (this was never implemented). The Congress of Vienna decided to divide the Duchy of Warsaw into three core territories: the Kingdom of Poland, the Free State of Kraków and the Grand Duchy of Posen; the latter was autonomous but was awarded to Prussia. The Kingdom of Poland and the Free State of Kraków were incorporated into the territory of the partitioning powers in accordance with international law and the decisions of the Congress of Vienna. The newly created Kingdom of Poland, also known as Congress Poland, developed into the territory of the defunct republic where Polishness could be actively cultivated with comparatively great freedom. It became the focus of Polish ideas related to culture and education, and the centre of Polish political and economic life, despite the very liberal constitution of 27 June 1845 imposed on it by Tsar Alexander I, who was also King of Poland.